PENGARUH METODE PEMBELAJARAN SISWA MEMPUNYAI PERTANYAAN DALAM MENINGKATKAN KEMAMPUAN MENULIS BERITA OLEH SISWA KELAS X SMA PRAYATNA MEDAN TAHUN PEMBELAJARAN 2012/2013 - Siti Sri Rahayu (Universitas Negeri Medan, 2012)
The research was motivated by the persistence of students who have difficulties in writing a news story, include difficulty putting the elements of news, keruntutan exposure, use short sentences and clear, kemenarikkan titles, as well as the correct use of spelling in the news that are customized by EYD (spelling in polishing) ukan. The difficulty arises due to lack of student interest and no innovation in the learning process. This indicates that the learning news writing achievement indicators do not meet the learning objectives. Therefore, the researchers tested the method intended to question student have in learning to write news. The method used in this study is quasi-experimental method with the one group pretest-posttest single group design performed on members of the population, namely the class X High School Private Prayatna field with the sample X1 grade 30 students as a class experiment. In this research, the experimental class were given the news writing skills test before and after using this method have student question. The results of the calculation of variance test group studied sample count obtained F = 1.50 and F table = 1.68. Price Fhitung <F table is 1.50 <1.68. It proves that the variance of the population is homogeneous. Calculation results obtained t0 t test outweigh the TTable 9.69> 2.04 at the 5% significance level and the calculation of nil hypothesis testing (H0) is rejected and the alternative hypothesis (Ha) is accepted. This proves that the method of student question have a positive influence high school students of class X Prayatna Field Learning Year 2012/2013. Keywords: Effect of method of question student have in learning to write news.